Effect of the load level on the resistance of composite slabs with steel decking under fire conditions - Piloto, P.A.G. (2020)
The fire resistance of composite slabs with steel decking, in Europe, is usually defined using simple calculation models provided by the Eurocode EN 1994-1-2. For assessing the methodology of these simple calculation methods, a new advanced calculation method is presented, using the software ANSYS. The numerical model is first validated with experimental data reported on bibliography and then a parametric analysis is conducted to better understand the effect of the load level on the composite structure under fire. The validation of the simulations consisted of three different models: the first model considers perfect contact between the steel deck and the concrete topping, and the two following models consider the existence of an air gap between these materials, acting as a thermal resistance on the temperature field through the thickness of the slab. The numerical results show good approximation to the experimental results, mainly when using the non-perfect contact model, reaching 3.88% and 16.91% of difference with respect to the insulation and load-bearing criteria, respectively. Based on the validation models, a parametric study is presented, modifying the load level from 10% up to 75%. New simple calculation models are presented to define the fire resistance of composite slabs, considering the load level, and the debonding effect between the concrete and the steel deck.